Stability of Corneal Totopography after Correction of Hyperopia by FS-LASIK: 3 Years of Follow-up - I. L. Kulikova; S. M. Pikusova; A. A. Anan’ev (Oftalʹmologiâ)
Purpose. To analyze changes of the corneal topography in the long-term period after hyperopic FS-LASIK in patients with low, moderate and high hyperopia.Patients and Methods. This retrospective non-randomized study included data of 174 patients (174 eyes). All patients were performed hyperopic FS-LASIK. All patients were divided into three groups. Group I included patients with low hyperopia (34 eyes), group II included patients with moderate hyperopia (97 eyes), group III included patients with high hyperopia (43 eyes). Before the surgery, the mean cycloplegic spherical equivalent in group I was +1.94 ± 0.61 D, in group II +3.8 ± 2.19 D, in group III +5.7 ± 0.9 D. The stability of corneal topography after surgery was analyzed: mean keratometry, Surface Asymmetry Index (SAI), Surface Regularity Index (SRI). The results were evaluated the day after the surgery, 1 month later, 6 months later, 1 year later and 3 years after the surgery.Results. There were no statistically significant changes in keratometry in groups I and II on the first day after surgery and 3 years later (p > 0.05). In group III, there was a statistically significant decrease in keratometry at 6 months after surgery by 1.35 ± 2.48. D (p = 0.003); however, keratometry remained stable for 3 years thereafter (p > 0.05). In groups I and II, SRI increased at all periods after surgery (p < 0.05), in group II there was an increase in SAI (p < 0.05), in group III, SRI and SAI increased at all periods after surgery (p < 0.05). Although the increase in the indices was statistically significant, it slightly exceeded the normal limits.Conclusions. After correction of low and moderate hyperopia by FS-LASIK, corneal topography remains stable for 3 years after surgery. Correction of high hyperopia is associated with gradual flattening of the cornea within six months after surgery, but then keratometry remains stable for 3 years. It is important to take it into account in clinical practice.